The Role of Polydimethylsiloxane in Suppressing the Evolution of Lipid Oxidation Products in Thermo-Oxidised Sunflower Oil: Influence of Stirring Processes - Ampem, Gilbert; Le Gresley, Adam; Grootveld, Martin; Naughton, Declan P. (Frontiers in Nutrition, 2021)
Suppressing the evolution of lipid oxidation products (LOPs) in commercially available culinary oils is considered to represent a valuable health-promoting incentive since these agents have cytotoxic and genotoxic properties and have been implicated in the pathogenesis of several chronic disease states. One agent used to suppress LOP formation is polydimethylsiloxane (PDMS). In this study, proton nuclear magnetic resonance (1H NMR) analysis was employed to evaluating the influence of increasing PDMS concentrations (6.25×10-7, 1.0×10-5, 0.025, 0.05, 0.1, 0.5, 1.0, 5.0 and 10.0 ppm) in either stirred or unstirred refined sunflower oil exposed to thermal stressing episodes continuously at 180°C for 300 min. with no oil replenishment. Results acquired showed that the extent of blockage of LOP generation was correlated with increasing concentrations of PDMS. The minimal level of added PDMS required to provide a statistically-significant protective role for both stirred and unstirred culinary oils when exposed to high frying temperatures was only 6.25 × 10-7 ppm.